Evidence for ΔpH surface component (ΔpH S) of proton motive force in ATP synthesis of mitochondria - Xiong, Jing-Wei; Zhu, Liping; Jiao, Xuanmao; Liu, Shu-Sen (Biochimica et biophysica acta. General subjects, 2010)
One of the central debates in membrane bioenergetics is whether proton-dependent energy coupling mechanisms are mediated exclusively by protonic transmembrane electrochemical potentials, as delocalized pmf, ΔµH +, or by more localized membrane surface proton pathways, as interfacial pmf, ΔµH S. We measure ∆pH S in rat liver mitoplasts energized by respiration or ATP hydrolysis by inserting pH sensitive fluorescein-phosphatidyl-ethanolamine(F-PE) into mitoplast surface. In the presence of rotenone and Ap5A, succinate oxidation induces a bi-phasic interfacial protonation on the mitoplast membranes, a fast phase followed by a slow one, and an interfacial pH decrease of 0.5 to 0.9 pH units of mitoplast with no simultaneous pH changes in the bulk. Antimycin A, other inhibitors or uncouplers of mitochondrial respiration prevent the decrease of mitoplast ∆pH S, supporting that ΔµH S is dependent and controlled by energization of mitoplast membranes. A quantitative assay of ATP synthesis coupled with ∆pH S of mitoplasts oxidizing succinate with malonate titration shows a parallel correlation between ATP synthesis, State 4 respiration and ∆pH S, but not with ∆ Ψ E. Our data substantiate ∆pH S as the primary energy source of pmf for mitochondrial ATP synthesis. Evidence and discussion concerning the relative importance and interplay of ∆pH S and ∆ Ψ E in mitochondrial bioenergetics are also presented.